The causal relationship between openness and economic growth: Empirical evidence in case of Pakistan - Sulaiman D. Muhammad; Adnan Hussain; Shoaib Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Evaluation of long run relationship of the openness policy and Pakistan's economic growth is the prime objective of the study. Two different econometric techniques i.e. Johnson co-integration technique and Error Correction Model are applied to estimate the relationship with annual data span from 1970 to 2012. Export, import and Foreign Direct Investment are taken as variables which show a broader sense of openness. The result of our study shows that there is a long run relationship between openness and economic growth with reference of Pakistan. Further, the study proofs the Export Led Growth hypothesis in case of Pakistan.
Keywords: 330; Openness; Economic growth and long-run relationship; Handelsliberalisierung; Wirtschaftswachstum; Kointegration; Pakistan